Soil compaction enhances the impact of microwave heating on seedling emergence - Hess, Manon C.M.; Buisson, Elise; Mesléard, François (Flora. Morphologie, Geobotanik, Oekophysiologie, 2019)
•Microwave soil heating reduces seedling emergence of several invasive and non-invasive species.•A species-specific sensitivity to microwave heating is highlighted.•Compacting soil increases the efficiency of microwave heating on seeds of several species. An innovative microwave-based process to control invasive species in the field is currently under development. We investigated the effect of soil compaction levels under three microwave treatment pairings of power and duration (2kW4 min, 2kW8min and 4kW4 min), on seedling emergence of a diverse seed bank and three major invasive species in Europe (bohemian knotweed, giant goldenrod and jimsonweed). When soil was compacted, the number of seedling emergences of dicotyledons was significantly reduced by the 2kW4 min treatment. Furthermore, while some dicotyledon and giant goldenrod’s seedling emergences were observed respectively in plain soil in the 4kW4 min and 2kW4 min treatments, no seedling was recorded in compacted soil for the same treatments. Our results suggest that compacting soil increases the efficiency of microwave heating on seeds. Soil compaction level should therefore be considered in the design of the final microwave-based process.